PRELIMINARY TRIALS ON TRANSPORT OF FRY OF HILSA ILISHA (HAMILTON) - De, D K; Nath, D; Sen, P R (Indian Journal of Fisheries, 2011)
Transport of live fish plays an important role in fish culture operation.At present certain cultivable species are transported successfully, reducing therate of mortality. But culture of few other important species; other than carps,is yet to be developed, because of problems being faced during transport. Theanadromous species Hilsa ilisha (Ham.), commonly known as hilsa, is one ofsuch species, forming a very important seasonal fishery in most of the principalriver systems of India (Pillay et al 1963). Hilsa ascends the freshwater stretchof rivers from the inshore areas of sea mainly for breeding (Hora 1938; Horaand Nair 1940; Jones and Menon 1951). Since the abundance of hilsa in differentriver systems fluctuates heavily (Gopalakrishnan and Ghosh 1971; Hora1940) there is an urgent need for conservation of this species by way of culturingin confined waters (Mojumdar 1939; Pillay 1955). However, the successin culture largely depends on the bulk-availability of hilsa seed and a dependablemethod of transport-technique.